1985
DOI: 10.1073/pnas.82.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of 10-kilobase DNA replication intermediates in cells treated with 3-aminobenzamide.

Abstract: During eukaryotic DNA synthesis there is formation of, in addition to Okazaki fragments, discrete 10-kilobase (kb) DNA replication intermediates. We have investigated the ligation of 10-kb DNA replication intermediates to high molecular weight DNA, using the drug 3-aminobenzamide, an inhibitor of poly(ADP-ribose) synthetase. In human melanoma cells treated with this inhibitor, there is an accumulation of 10-kb DNA. In contrast, in cells treated with aphidicolin, which inhibits DNA polymerase a, there is contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The data are essentially the same as those published earlier (Lonn and Lonn, 1983). Furthermore, earlier experiments have shown that the Okazaki fragments are joined to form 10-kb DNA intermediates, which later give rise to high-molecular-weight DNA (Lonn and Lonn, 1985).…”
Section: Medium Supplemented With 10% Fcssupporting
confidence: 86%
See 1 more Smart Citation
“…The data are essentially the same as those published earlier (Lonn and Lonn, 1983). Furthermore, earlier experiments have shown that the Okazaki fragments are joined to form 10-kb DNA intermediates, which later give rise to high-molecular-weight DNA (Lonn and Lonn, 1985).…”
Section: Medium Supplemented With 10% Fcssupporting
confidence: 86%
“…In different cells different results were obtained on the increase in size of nascent DNA, with a discontinous increase in primary cultures of mouse embryo cells (Kowalski and Cheevers, 1976) and a continuous increase in C3H 10T112 cells (Cordeiro-Stohne and Kaufman, 1985). In some cells long-lived DNA replication intermediates have been detected (Funderud et al, 1978;Lonn and Lonn, 1985), which do not exist in other cells (Cordeiro-Stohne and Kaufman, 1985).…”
mentioning
confidence: 99%
“…It is known that alterations of chromatin structure by poly(ADP-ribose) synthetase influence the activity of DNA ligases [7]. In agreement with this we have shown earlier that there is an accumulation of large DNA replication intermediates (10-kb DNA) in human melanoma cells treated with 3-AB [8]. We wished to examine whether this accumulation interferes with the appearance of the post-elongation-stage DNA and the conversion of the new DNA to mature chromatin.…”
mentioning
confidence: 54%
“…There has been much discussion about the roles played by poly-ADP ribosylation of proteins in various biological functions, including the repair of chemically as well as physically damaged DNA in mammalian cells (4,5,9). Poly-ADP ribosylation has also been implicated in cellular differentiation and replication (10,15,24). Despite numerous reports, mostly concerning biochemical analysis of the reaction with purified poly(ADP-ribose) polymerase, little is known about how poly-ADP ribosylation is involved in these biological functions.…”
Section: Discussionmentioning
confidence: 99%